(untitled) (BIRDEM Medical Journal, 2020)
Heerfordt’s syndrome – the combination of facial palsy, parotid swelling, anterior uveitis and fever, is a rare manifestation of sarcoidosis. Here, we present case history of a patient with bilateral lower motor neuron facial nerve palsy, who was found to have bilateral parotid gland swelling and bilateral hilar lymphadenopathy. Computed tomography guided fine needle aspiration cytology from hilar lymph node findings were consistent with sarcoidosis. Subsequently, based on clinical features and cytological findings, the case was diagnosed as incomplete Heerfordt’s syndrome. Birdem Med J 2021; 11(1): 67-69